Becoming like them: Sociological Analysis of Celebrity Dress-Style and Student Dressing Behaviour within Selected Universities in Benin City, Edo State, Nigeria - Ojo, Divinefavour; Alenkhe, Augustine Odianonsen (NIU Journal of Social Sciences, 2025)
Dressing has become a lifestyle especially among young adults, whose external influence cut an image from actors and celebrities who often act as idols to their behaviour. This study examines the relationship between celebrity dressing styles and students’ clothing choices within the university environment. The Herbert Kelman Social influence theory was adopted for the study as it established the nexus between the interplay of normative lifestyle and imitation among students. Being an explanatory and a cross-sectional research design, the study triangulated a mixed method of data collection (qualitative and quantitative) using a semi-structured questionnaire and in-depth interview guide on a one-time survey method in 2 selected universities (namely: University of Benin and Benson Idahosa University). 240 respondents were systematically selected using a multi-stage sampling technique. It was discovered that most of the lifestyles of the students were tailored in line with their favourite celebrities and role models. Secondly, imitating friends’ dressing styles has become a norm among students due to the confidence it creates and sometimes alters the student’s lifestyle. The study therefore advocates that universities and related tertiary institutions should regulate the dressing behaviour of students to reflect the ideal standard behaviour after schooling. Keywords: Behaviour; Celebrity; Dressing; lifestyle; Students